2022
DOI: 10.1016/j.resuscitation.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice providers in critical care improve team performances. A post-hoc analysis of the BASIC trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…However, when we assess the performance of APPs by process outcomes, the handoff CEX recipient scale, an assessment of the RRT procedure in several domains, such as content, organization, judgment and communication as assessed by an experienced intensivist, did show a better performance of the APPs. This better performance of the APP-led teams on the CEX recipient scale is in line with a recent study, which found improved performances in the non-technical skills of APPs compared to physicians [ 17 ]. The CEX recipient scale outcome acknowledges the impression that an experienced APP performs on a higher level than an experienced resident.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, when we assess the performance of APPs by process outcomes, the handoff CEX recipient scale, an assessment of the RRT procedure in several domains, such as content, organization, judgment and communication as assessed by an experienced intensivist, did show a better performance of the APPs. This better performance of the APP-led teams on the CEX recipient scale is in line with a recent study, which found improved performances in the non-technical skills of APPs compared to physicians [ 17 ]. The CEX recipient scale outcome acknowledges the impression that an experienced APP performs on a higher level than an experienced resident.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study using propensity score matching found that the participation of an APP in an RRT resulted in a decreased length of hospital stay [ 16 ]. Moreover, a recent study showed that APPs often provide direct additional value compared to a physician, as it measured process-related outcomes of APPs in a simulated rapid response team environment and showed that an APP might perform better than a medical resident (MR) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%